In silico ligand binding studies of cyanogenic beta-glucosidase, dhurrinase-2 from Sorghum bicolor - Mahajan, Chavi; Patel, Krunal; Khan, Bashir Mohammad; Rawal, Shuban S. (Journal of Molecular Modeling, 2015)
Dhurrinase, a cyanogenic beta-glucosidase from Sorghum bicolor is the key enzyme responsible for the hydrolysis of dhurrin to produce toxic hydrogen cyanide, as a part of plant defence mechanism. Dhurrinase 1 (SbDhr1) and dhurrinase 2 (SbDhr2), two isozymes have been isolated and characterized from S. bicolor. However, there is no information in the literature about the three dimensional (3D) structure of SbDhr2 and molecular interactions involved between the protein and ligand. In this study, the three dimensional structure of SbDhr2 was built based on homology modeling by using the X-ray crystallographic structure of its close homologue SbDhr1 as the template. The generated 3D model was energy minimized and the quality was validated by Ramachndran plot, various bioinformatic tools and their relevant parameters. Stability, folding-unfolding and flexibility of the modeled SbDhr2 was evaluated on the basis of RMSD, radius of gyration (R-g) and RMSF values respectively, obtained through molecular dynamic (MD) simulation. Further, molecular docking was performed with its natural substrate dhurrin, one substrate analogue, three un-natural substrates, and one inhibitor. Analysis of molecular interactions in the SbDhr2-ligand complexes revealed the key amino acid residues responsible to stabilize the ligands within the binding pocket through non-bonded interactions and some of them were found to be conserved (Glu239, Tyr381, Trp426, Glu454, Trp511). Reasonably broader substrate specificity of SbDhr2 was explained through the wider entrance passage observed in comparison to SbDhr1.
Keywords: beta-Glucosidase; Dhurrinase; Molecular docking; Molecular dynamic simulation; Sorghum bicolor

Insights into the unfolding pathway and identification of thermally sensitive regions of phytase from aspergillus niger by molecular dynamics simulations - Kumar, Kapil; Patel, Krunal; Agrawal, Dinesh C.; Khire, Jayant Malhar (Journal of Molecular Modeling, 2015)
Thermal stability is of great importance in the application of commercial phytases. Phytase A (PhyA) is a monomeric protein comprising twelve alpha-helices and ten beta-sheets. Comparative molecular dynamics (MD) simulations (at 310, 350, 400, and 500 K) revealed that the thermal stability of PhyA from Aspergillus niger (A. niger) is associated with its conformational rigidity. The most thermally sensitive regions were identified as loops 8 (residues 83-106), 10 (161174), 14 (224-230), 17 (306-331), and 24 (442-444), which are present on the surface of the protein. It was observed that solvent-exposed loops denature before or show higher flexibility than buried residues. We observed that PhyA begins to unfold at loops 8 and 14, which further extends to loop 24 at the C-terminus. The intense movement of loop 8 causes the helix H2 and beta-sheet B3 to fluctuate at high temperature. The high flexibility of the H2, H10, and H12 helices at high temperature resulted in complete denaturation. The high mobility of loop 14 easily transfers to the adjacent helices H7, H8, and H9, which fluctuate and partially unfold at high temperature (500 K). It was also observed that the salt bridges Asp110-Lys149, Asp205-Lys277, Asp335-Arg136, Asp416-Arg420, and Glu387-Arg400 are important influences on the structural stability but not the thermostability, as the lengths of these salt bridges did not increase with rising temperature. The salt bridges Glu125-Arg163, Asp299-Arg136, Asp266-Arg219, Asp339-Lys278, Asp335-Arg136, and Asp424-Arg428 are all important for thermostability, as the lengths of these bridges increased dramatically with increasing temperature. Here, for the first time, we have computationally identified the thermolabile regions of PhyA, and this information could be used to engineer novel thermostable phytases. Numerous homologous phytases of fungal as well as bacterial origin are known, and these homologs show high sequence similarity. Our findings could prove useful in attempts to increase the thermostability of homologous phytases via protein engineering.
Keywords: Conformational dynamics; Molecular dynamics simulations; PhytaseA; Structurally weak regions; Thermostability